Fbxo42 promotes the degradation of Ataxin-2 granules to trigger terminal Xbp1 signaling. - Santos, C.C.; Schweizer, N.; Cairrão, F.; Ramirez, J.; Osinalde, N.; Yang, M.; Gaspar, C.J.; Rasheva, V.I.; Trigo, M.L.; Hensel, Z.; Adrain, C.; Cordeiro, T.N.; et al. (Nature communications, 2025)
The Unfolded Protein Response (UPR) is activated by the accumulation of misfolded proteins in the Endoplasmic Reticulum (ER), a condition known as ER stress. Prolonged ER stress and UPR activation cause cell death, by mechanisms that remain poorly understood. Here, we report that regulation of Ataxin-2 by Fbxo42 is a crucial step during UPR-induced cell death. From a genetic screen in Drosophila, we identify loss of function mutations in Fbxo42 that suppress cell death and retinal degeneration induced by the overexpression of Xbp1[spliced], an important mediator of the UPR. We identify the RNA binding protein Ataxin-2 as a substrate of Fbxo42, which, as part of a Skp-A/Cullin-1 complex, promotes the ubiquitylation and degradation of Ataxin-2. Upon ER-stress, the mRNA of Xbp1 is sequestered and stabilized in Ataxin-2 granules, where it remains untranslated. Fbxo42 recruitment to these granules promotes the degradation of Ataxin-2, allowing for the translation of Xbp1 mRNA and triggering cell death during the terminal stages of UPR activation.